Study on Impact of Tertiary Care Baby Friendly Hospital on Exclusive Breast Feeding and Child Health - Das, Nanda Lal; Khan, Md Fazlul Kader; Azam, Md Shaiful; Rouf, MA; Sultana, Merina; Afroz, Sakina Shab; Islam, Khandaker Tarequl; Alam, Md Shafiul (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Initiation of breast-feeding within 1hour after birth has been associated with reduced neonatal mortality. Baby Friendly Hospital Initiative has profound effects on appropriate practice of BF and thus helps to reduce infant mortality and morbidity. Objective: This study was conductedin the dept.Gynae & Obs and Dept of Paediatrics of Shaheed Suhrawardy Medical College Hospital,Dhaka, to observe the rates of exclusive breast feeding and child health status after cancelling from Baby Friendly Hospital Methodology: 100 term babies of normal birth weight irrespective of sex, born in Sh.SMCH by NVD or caesarian section were included. Data was collected from the mother with a pretested questionnaire at postnatal period, at 6th week, 14th week & 6th month of age. Result: The mean age of studiednewborn (100) was 20.02±19.54 hours. All the infants started breast feeding after birth and among them fifty six percent initiated with in 1 hour. Fifty five percent mothers were fed breast milk more than 8 times of her baby in last 24 hours. Difficulty in breast feeding was found in 36(36.0%) infants, which was resolved mostly (94%) by nurse. Exclusive breastfeeding was found in 100% of infants during discharge from hospital. In 1st and 2nd follow up 95(95.0%) and 89(89.0%) infants were exclusively breastfed. In 3rd follow up at last week of 6th month 78(78.0%) infants were exclusively breast fed. Five(5%) and six(6%) infants received supplementary food in 1st and 2nd follow up respectively. In last follow up the number were eleven (11%) and the total number was 22(22%).The causes of supplementation were crying of baby due to perceived insufficient breast milk and job of the mother in 1st& 2nd and 3rd visit respectively. Weight was significantly (p<0.05) higher in exclusive breast feeding group than the non EBF group and sickness were also more in non EBF group. Conclusion: Exclusive breast feeding was found in 78.0% of infants upto last week of 6 months. Crying of baby due to perception of insufficient breast milk and joining in outside job of the mother were the causes of introduction of formula milk in the 1st,2nd and 3rd visit respectively. Weight gain and sickness were significantly less in EBF group than in non EBF group. J Shaheed Suhrawardy Med Coll 2021; 13(2): 164-170